The Role of the Islamic Religious Education Curriculum in Character Development: A Study of Challenges and Educational Impact in Indonesia - Alhamuddin; Ikin Asikin (Universitas Muhammadiyah Jember, 2025)
This study aims to analyze the role of the Islamic Religious Education (IRE) curriculum in shaping character education in Indonesia. In the context of national education reform and the moral challenges facing youth, the curriculum is expected to deliver not only religious knowledge but also the internalization of character values relevant to real-life experiences. This research employed a qualitative method through document analysis of curriculum guidelines, textbooks, and teacher manuals at the secondary school level. The findings reveal that character values such as honesty, responsibility, empathy, and discipline are normatively embedded in the curriculum. However, a gap exists between the moral concepts being taught and the real-life contexts students face. The curriculum tends to be declarative and lacks pedagogical approaches that promote reflection and contextual application. Furthermore, the evaluation of students’ character development is not systematically integrated into the assessment process. The study recommends the development of more dialogic, experiential, and context-based teaching strategies, as well as enhanced teacher training. Accordingly, the Islamic Religious Education curriculum has the potential to play a significant role in shaping students’ character in a holistic and socially relevant manner.